Radiolabelling rituximab with 99mTc in three steps procedure. (27th May 2015) - Fontan, Charlotte; Bezombes, Christine; Salabert, Anne Sophie; Costes, Julien; Lopez, Raphael; Fournie, Jean‐Jacques; Avet‐Loiseau, Hervé; Coulais, Yvon; Payoux, Pierre; Tafani, Mathieu
<x xml:space="preserve">Abstract</x> Lymphomas are the most frequent haematological malignancy. In non‐Hodgkin's lymphomas (NHL), more than 90% of tumor cells express the cluster of differentiation (CD) 20 antigen. At the end of frontline therapy, the evaluation of remission is based on computed tomography (CT) and positron emission tomography coupled with computer tomography (PET/CT) with [18F]‐fluorodeoxyglucose ([18F]FDG). Unfortunately, these techniques are not specific and cannot distinguish residual active tumor from inflammation. The aim of this study was to develop a specific radiotracer of NHL CD 20+ cells for clinical applications. The radiolabelling technique presented, based on the use of tricarbonyl compound, does not include an antibody reduction because this step could damage the protein. Actually, rituximab, an anti‐CD 20 chimeric antibody used for the treatment of these NHL, was radiolabelled with Isolink® 99mTc‐tricarbonyl compound in a three‐step procedure without using a specific antibody reducer. Radiolabelling yield was greater than 97%. In vitro experiments showed a conservation of antibody integrity. In vivo experiments using Single‐photon emission computed tomography/CT showed significant tumor targeting 24 h after injection of the radiotracer. It was consequently possible to develop an immunoradiolabelling method to specifically detect the residual disease. As this procedure is fast, reproducible and gentle, it will be possible to comply with Good Manufacturing Practices.